Model Prokrastinasi Akademik Pada Mahasantri: Analisis Struktural Equation Model - Bahrodin, Ariga; Bafadal, Ibrahim; Eva, Nur; Farida, Ika Andrini (Al-Ulum, 2024)
This study examines the formation of academic procrastination in the absence of the influence of peers. This study employed a correlational quantitative approach involving a sample of 425 mahasantri, selected through the cluster random sampling technique. This study used four instruments. The Academic Procrastination Scale (α = 0.971) was employed to assess academic procrastination, the Self-Regulated Learning Questionnaire (α = 0.937) was utilized to evaluate self-regulated learning, the Positive Peer Influence Inventory (α = 0.882) was utilized to assess peer influence, and the General Self-Efficacy Scale (α = 0.788) was utilized to assess self-efficacy. The data were analyzed using structural equation modeling with AMOS. The results showed chi square value = 131.924 (p <0.05), GFI = 0.968, AGFI = 0.952, CFI = 0.994, TLI = 0.992, RMSEA = 0.030 and NFI = 0.981.